Logistic-Empirical Model For Students Susceptibility To Harmful Einstellung Effect in Mathematics Instruction - Chinedu Obasi (International Journal of Trends in Mathematics Education Research, 2020)
Harmful Einstellung effect creates a serious source of aversion for students in Mathematics. It may not be clear whether students fail Mathematics due to lack of knowledge or due to aversion arising from Einstellung effect. This study therefore investigated students’ susceptibility to harmful Einstellung effect in Mathematics instruction using logistic-empirical model approach. A cross-section of senior secondary school (SS 2) students of Alvana Model Secondary School Owerri, Imo State numbering 93 were continuously observed (using direct observational technique with observation schedule) and surveyed to decipher their susceptibility to harmful Einstellung effect. The result indicates increasing susceptibility to harmful Einstellung effect. That is, a high prevalence of Einstellung phenomenon was observed among students. It is important to note that this has consequently resulted in the increase of aversive behaviour in Mathematics learning. It was recommended among others that teachers should inform the students about harmful Einstellung effect during teaching and encourage them to think critically about any mathematical problem before finding solutions. Also, teachers should adopt some approaches when teaching Mathematics, such as, delayed formalization approach and target task approach.